A Numerical Investigation of Laser Beam Welding of Stainless Steel Sheets with a Gap - Michele Buttazzoni; Constantin Zenz; Andreas Otto; Rodrigo Gómez Vázquez; Gerhard Liedl; Jorge Luis Arias (Applied Sciences, 2021)
Keyhole laser beam welding (LBW) of 304L stainless steel sheets with a gap in between was numerically simulated with a three-dimensional, transient, multi-physical model for laser material processing based on the finite volume method (FVM). First, the model’s ability to reproduce experimental results on a relatively coarse computational mesh within reasonable computing time, so as to serve as process optimization tool, is presented. An example of process optimization is shown, wherein a given set of weld seam quality criteria is fulfilled by iteratively optimizing a secondary laser beam. The relatively coarse mesh, in combination with a good model calibration for the experimental conditions, allows for sufficiently fast simulations to use this approach for optimization tasks. Finally, using a finer spatial and temporal discretization, the dynamic processes in the vicinity of the keyhole leading to the formation of pores are investigated. The physical phenomena predicted by the simulation are coherent with experimental observations found in literature.